2022
DOI: 10.1007/s00264-022-05402-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of heterotopic ossification following hip arthroscopy is low: considerations for routine prophylaxis

Abstract: Purpose This scoping review aims to map and summarise the available literature on heterotopic ossification (HO) following hip arthroscopy, with particular focus on incidence, distribution as per Brooker classification, efficacy of prophylactic measures and factors that may influence the likelihood of production of HO. Methods A computer-based search was performed on PubMed, Embase, Emcare, Cinahl, ISI web of science and Scopus using the terms ‘heterotopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 89 publications
1
2
0
Order By: Relevance
“…11,[25][26][27][28][29][30][31][32] Several studies have demonstrated that the use of NSAIDs diminishes the rate of HO after hip arthroscopy. 3,4,33 Bedi et al described an important HO rate decrease from 8.1 to 1.8% with the systematic use of NSAIDs, 11 similar to the results showed by Randelli et al, with a notable decrease from 33 to 0% after the prophylactic use of NSAIDs for 3 weeks after the arthroscopic surgery. 25 However, there is a concern regarding the use of NSAIDs due to their intrinsic side effects, especially in older patients, that can cause gastrointestinal problems, bleedings or renal alterations, and blood pressure modifications.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…11,[25][26][27][28][29][30][31][32] Several studies have demonstrated that the use of NSAIDs diminishes the rate of HO after hip arthroscopy. 3,4,33 Bedi et al described an important HO rate decrease from 8.1 to 1.8% with the systematic use of NSAIDs, 11 similar to the results showed by Randelli et al, with a notable decrease from 33 to 0% after the prophylactic use of NSAIDs for 3 weeks after the arthroscopic surgery. 25 However, there is a concern regarding the use of NSAIDs due to their intrinsic side effects, especially in older patients, that can cause gastrointestinal problems, bleedings or renal alterations, and blood pressure modifications.…”
Section: Discussionsupporting
confidence: 65%
“…HO has been observed in 0 to 44% of hip arthroscopies and 2 to 90% of total hip replacements. 1 2 3 4 5 6 7 8 9 10 While most of the patients with HO remain asymptomatic, patients with large ossifications or concomitant femoroacetabular impingement can present stiffness and discomfort, for which surgical treatment is indicated. 1 11 12 13 …”
mentioning
confidence: 99%
“…Despite the evidence for the efficacy of prophylaxis in reducing the incidence of HO, its clinical importance is still debated in the literature [ 16 , 26 , 27 ]. Kurz et al [ 12 ] in their review reported that only 25% of HO post-hip arthroscopy were symptomatic.…”
Section: Discussionmentioning
confidence: 99%